Differences in career paths and attributes of pharmacists completing a community pharmacy residency program (CPRP) - Timothy R. Ulbrich; Alex Adams; David R. Bright; Donald L. Sullivan; Evan Schnur; D. Todd Bess; James Owen; Lynette Bradley-Baker (University of Minnesota Libraries Publishing, 2014)
Objective: To determine any differences in career paths and career attributes of pharmacists who have completed a PGY1 community pharmacy residency program (CPRP) as compared to those that have not completed a PGY1 CPRP. Methods: A web-based survey evaluating various aspects of community pharmacists' careers was distributed to 274 CPRP graduates in addition to a random sample of 7,376 community pharmacists. The survey contained 32 questions evaluating various career attributes. Questions that assessed level of agreement were on a 6-point Likert-type Scale (1=strongly disagree; 6=strongly agree). Results: A total of 353 participants completed the survey, with 224 indicating that they had not completed a CPRP. Pharmacists who completed a CPRP responded that they spend significantly more time on patient care services, teaching, and research, and spend less time dispensing medications compared to those that have not completed a CPRP. Compared to those that did not complete a CPRP, CPRP graduates were less likely to agree that current level of workload negatively impacts job performance, motivation to work, job satisfaction, mental/emotional health, and physical health. Conclusion: Pharmacists completing a CPRP noted significant differences in their current employment and job responsibilities. Additional expansion and education regarding the importance of CPRPs should be considered.   Type: Original Research